Navigating the American education system : four Latino success stories - Vargas, Manuel P. (Emerald Publishing Limited : Information Age Publishing, inc., 2020)
"Navigating the American Education System: Four Latino Success Stories showcases the educational journey of four Latino/a men and women who navigated the American education system successfully. Their success is significant given the multiple and varied challenges that most Latinos/as encounter throughout the K-20 educational continuum. The purpose of this book is not only to show and tell, but to describe ordinary people attaining extraordinary results, who might also stand as good role models for the youngest- and fastest-growing group-Latinos/as-in this country. Researchers of this topic offer compelling statistics, such the following projection: Out of 100 Latino/a students, a few more than 50 will finish high school; out of this number, five will enroll in college; and out of the original 100, less than one percent will complete a doctorate. While the causes of low academic attainment for Latinos may vary, including limited financial resources and cultural differences, the lack of Latino role models in K-20 education may be a significant contributing factor"--